Prevalence and Antimicrobial Resistance of Campylobacter Species in Diarrheal Patients in Mymensingh, Bangladesh. (4th August 2021) - Rahman, Md. Ashikur; Paul, Priyanka Rani; Hoque, Nazmul; Islam, Sk Shaheenur; Haque, A. K. M. Ziaul; Sikder, Mahmudul Hasan; Matin, Aminul; Yamasaki, Shinji; Kabir, S. M. Lutful
Abstract : Campylobacter enteritis is the leading cause of gastroenteritis in humans worldwide including Bangladesh. The objectives of this study were to estimate the prevalence and antimicrobial-resistance status of Campylobacter spp. in human diarrheal samples collected from Surya Kanta Hospital, Mymensingh, Bangladesh. In this study, we evaluated a total of 330 clinical samples for the presence Campylobacter spp. via cultural and biochemical tests and molecular assays. Furthermore, antimicrobial susceptibility testing for Campylobacter species was accomplished by the standard agar disc diffusion technique against eight commercially available antimicrobial agents. A pretested semistructured questionnaire was used to capture the data on socioanthropological factors from the diarrheal patients. Pearson's chi-square test was performed, and a p value of <0.05 was considered for the level of significance. Nearly one in three diarrheal patients admitted in this hospital were infected with Campylobacter spp. Overall prevalence of Campylobacter spp. was estimated to be 31.5% (104/330) that comprised the prevalence of C. jejuni, 21.8% (n = 72 ), and C. coli, 9.6% (n = 32 ). Among the positive cases, the prevalence of Campylobacter was higher in the age group 0-5 years (52%) followed by 6-18 years (42.7%), 19-40 years (34.0%), 41-60 years (25.4%), and >60 years (10.5%). Age, family level's personal hygiene, and involvement with animal husbandry were captured as potential determinants to be associated with the Campylobacter positive status. Among the isolates, 27.3% (n = 20 ) of C. jejuni and 31.2% (n = 10 ) of C. coli demonstrated as multidrug-resistant (MDR) to three or more antimicrobial agents. The present study shows that Campylobacter spp. is most prevalent among the hospital-admitted diarrheal patients, and proper measures should be taken to reduce the burden focusing on the potential determinants.